Vital Hepatic Lymphoma Residuum or Excessive Immune Response? Challenging Treatment Decisions in a Patient With Systemic Lupus Erythematosus and Liver-Dominant Diffuse Large B-Cell Lymphoma: Case Report - Kurch, Lars; Georgi, Thomas W.; Monecke, Astrid; Seehofer, Daniel; Borte, Gudrun; Sabri, Osama; Kluge, Regine; Heyn, Simone; Pierer, Matthias; Platzbecker, Uwe; Kayser, Sabine (Frontiers in Oncology, 2022)
A 28-year-old female patient with active and difficult-to-treat systemic lupus erythematosus (SLE) was diagnosed with liver-dominant diffuse large B-cell lymphoma. Repeated response 18F-FDG-PET studies showed persistently high, and, despite intensified immunochemotherapy, further increasing metabolic activity of one of the hepatic lymphoma residuals, whereas all other initial lymphoma manifestations had achieved complete metabolic remission. As biopsy of the 18F-FDG-PET-positive liver residual turned out to be inconclusive, complete resection was performed. Subsequent histopathological examination, however, revealed only necrotic tissue. Thus, no further lymphoma treatment was scheduled. The patient undergoes regular surveillance and is disease-free 13 months after resection. Similarly, treatment of SLE is no longer required due to lack of activity already after the first two cycles of lymphoma treatment. The case shows how closely SLE and diffuse large B-cell lymphoma can be connected and stresses the importance of interdisciplinary treatment approaches. In future, artificial intelligence may help to further classify 18F-FDG-PET-positive lymphoma residuals. This could lead to an increase of the positive predictive value of interim- and end-of-treatment 18F-FDG-PET. The patient’s point of view enables another instructive perspective on the course of treatment, which often remains hidden to treating physicians due to lack of time in clinical routine.